Penerapan Model Numbered Head Together Berbantuan Media PowerPoint Untuk Meningkatkan Aktivitas Belajar - Alexon, Alexon; Supriatna, Irfan; Akhmad, Gusti (UNIB Press, 2023)
The Study aimed to improve students’ activities and learning achievement in class V SDN 17 Bengkulu City by applying Numbered Head Together (NHT) model assisted by PowerPoint. This study was an action research and was conducted in 2 cycles which each cycle consisted of for stages including: (1) Planning; (2) Action; (3) Observation; (4) Reflection. The subjects were a teacher and 23 students consisted of 10 male students and 13 female. The instruments were observation sheets and test sheets. The analysis for NHT model assisted by PowerPoint and learning activities observation data were analyzed by applying mean score formula, highest score, lowest score, score differentiation, and approximate score for each criteria. Students’ learning achievement in knowledge aspect was analyzed using mean score formula and the classical learning percentage. Result of NHT model assisted by PowerPoint application on cycle I had gotten adequate category improved getting very good category on cycle II. Result of learning activities on cycle I had categorized as adequate improved to good on cycle II. The student’s learning achievement for Bahasa Indonesia subject on cycle I had gotten the classical learning mastery by 52,1%. Improved on cycle II with the classical learning mastery by 86.9%. For Science subject, the classical learning mastery had been 47.1% on cycle I improved on cycle II with the classical learning mastery by 78,2%. Thus, applying Numbered Head Together model assisted by PowerPoint improved the students’ activities and learning achievement in the Class V SDN 17 Bengkulu City.